Chemical Heterointerface Engineering on Hybrid Electrode Materials for Electrochemical Energy Storage (Small Methods 8/2021). Issue 8 (12th August 2021) - Li, Wenbin; Song, Qianqian; Li, Matthew; Yuan, Yifei; Zhang, Jianhua; Wang, Ni; Yang, Zihao; Huang, Jianfeng; Lu, Jun; Li, Xifei
Abstract : Front Cover In article number 2100444, Lu, Li, and co‐workers provide a new perspective to understand the intrinsic behavior of chemical heterointerfaces on hybrid electrode materials, highlight the strategies for introducing chemical heterointerfaces, introduce the three enhancement effects of chemical heterointerfaces on electrochemical performance, and summarize the recent progress of chemical heterointerfaces engineering in metal‐ion batteries, supercapacitors, and Li‐S batteries.